How to Stage a Raid: Police, media and the master narrative of trafficking - Annie Hill (Anti-Trafficking Review, 2016)
The article analyses a UK police raid in 2005 on a West Midlands massage parlour called Cuddles. This raid to rescue victims of trafficking reflects a state approach that, despite police claims to the media, is not victim-centred. In publicising the raid, the police and media participate in discriminatory practices that reproduce a master narrative of trafficking and cause harm to the women the state purports to protect. This article examines details of the Cuddles raid and its aftermath that are obscured in the official account and offers an alternative interpretation of raid photographs circulated by the media. Findings suggest the rights of women targeted in raids are disregarded and the harm they experience dismissed in order to amplify the state’s anti-trafficking agenda. Bringing a fuller story to the fore reveals that raids tell subjugated stories and create spectacles that can challenge the master narrative of trafficking disseminated to the British public.